Geobotanical survey of wood-pasture habitats in Europe: diversity, threats and conservation - Bergmeier, Erwin; Petermann, Jörg; Schröder, Eckhard (Biodiversity and Conservation, 2010)
Agro-silvopastoral land-use has a long tradition throughout Europe. Depending on the region, wood-pasture occurs as vanishing relic of historical land-use, or still more or less widespread as multiple-use rangeland. A new development is that former intensively managed land is being left to evolve towards wood-pasture as an economically and ecologically favourable alternative. In a review of European wood-pasture habitats we distinguish 24 types based on the geobotanical criteria of region, structure, land-use and tree species composition. The European wood-pasture types may be classiﬁed as hemiboreal and boreal (4 types), nemoral old-growth (7), nemoral scrub and coppice (5), meridional old-growth (2), meridional scrub and coppice (4), and grazed orchards (2). Wood-pasture forms part of the cultural heritage of Europe, and may add signiﬁcantly to the preservation of regional biodiversity. The role of wood-pasture in ecological restoration planning and the possibilities of maintaining or enhancing features of wood-pasture deserve more recognition. Many wood-pastures suffer from regeneration failure and are over-mature. Other threats to wood-pasture include abandonment, intensiﬁcation, oak disease, overgrazing and clearance. In the European Union Habitats Directive, woodpasture habitats are represented but rather inconsistently. We suggest neglected woodpasture habitat types to be considered for inclusion. Wood-pasture may form an important element for the economic integrity of rural areas aiming to improve ecological quality‚ provided they are managed sustainably
Keywords: Agroforestry; Dehesa; Habitats directive; Hudewald; Pasture-woodland; Silvopastoralism; Traditional land-use